The Circular Economy: Analysis Based on The Theory of Resources and Capabilities - Vargas-Hernández, José G.; Medrano, Marlene de Jesús Morales (Revista Gestão & Sustentabilidade, 2019)
The purpose of this document is to analyze the Circular Economy (CE) model from the point of view of the resources and capacities of the organization. How is the application of the Circular Economy model related to Strategic Management? At first glance, it seems that the CE is operating within an operational level with a social impact, but it also has implications that allow us to think that it can be used as an internal resource of the company that, if applied in the right way, can become a competitive advantage, in other words, the application of the CE is related to Strategic Management through the point of view based on resources and capabilities. Therefore, the present investigation has a descriptive-correlational nature, which was analyzed through Peng’s VRIO framework.